Chlorpyrifos and Malathion have opposite effects on behaviors and brain size that are not correlated to changes in AChE activity - Richendrfer, Holly (Neurotoxicology, 2015)
Organophosphates, a type of neurotoxicant pesticide, are used globally for the treatment of pests on croplands and are therefore found in a large number of conventional foods. These pesticides are harmful and potentially deadly if ingested or inhaled in large quantities by causing a significant reduction in acetylcholinesterase (AChE) activity in the central and peripheral nervous system. However, much less is known about the effects of exposure to small quantities of the pesticides on neural systems and behavior during development. In the current study we used zebrafish larvae in order to determine the effects of two of the most widely used organophosphates, chlorpyrifos and malathion, on zebrafish behavior and AChE activity. Embryos and larvae were exposed to the organophosphates during different time points in development and then tested at 5 days post-fertilization for behavioral, neurodevelopmental and AChE abnormalities. The results of the study indicate that chlorpyrifos and malathion cause opposing behaviors in the larvae such as swim speed (hypoactivity vs. hyperactivity) and rest. Additionally, the pesticides affect only certain behaviors, such as thigmotaxis, during specific time points in development that are unrelated to changes in AChE activity. Larvae treated with malathion but not chlorpyrifos also had significantly smaller forebrain and hindbrain regions compared to controls by 5 days post-fertilization. We conclude that exposure to very low concentrations of organophosphate pesticides during development cause abnormalities in behavior and brain size.